2011
DOI: 10.1177/014556131109001218
|View full text |Cite
|
Sign up to set email alerts
|

Tooth in the Nose: Unusual Presentation of a Misdiagnosed Maxillary Ossifying Fibroma

Abstract: Fibro-osseous lesions involving the paranasal sinuses are uncommon, and making a determination of their histologic type is challenging. Correlating clinical and surgical fi ndings with radiologic and histologic characteristics is essential for making a defi nitive diagnosis. We describe a case of misdiagnosed maxillary ossifying fi broma presenting as a solitary mass that completely fi lled and enlarged the left maxillary sinus. Another interesting fi nding was the presence of a molar tooth embedded in the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In this investigation, zygomatic fractures were noted in 31.6% of the fractures, while 17.8% to 33.3% were reported by other authors. [ 4 18 19 20 ] These fractures were almost equally distributed between zygomatic buttress fractures and isolated zygomatic arch. On the other hand, Agarwal et al ., who conducted a similar study in India, found that zygomatic fractures accounted for only 8.7% of all analyzed midface fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, zygomatic fractures were noted in 31.6% of the fractures, while 17.8% to 33.3% were reported by other authors. [ 4 18 19 20 ] These fractures were almost equally distributed between zygomatic buttress fractures and isolated zygomatic arch. On the other hand, Agarwal et al ., who conducted a similar study in India, found that zygomatic fractures accounted for only 8.7% of all analyzed midface fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Global morbidity and mortality from trauma exceed that of HIV/AIDS, malaria, and tuberculosis combined, yet trauma and its management garner little comparative attention 1 . Craniomaxillofacial (CMF) fractures represent a significant component of overall trauma in low‐ and middle‐income countries (LMICs) 2 . Open reduction internal fixation (ORIF) is the gold standard for CMF fractures, but patients in LMICs must purchase their own plating supplies.…”
mentioning
confidence: 99%
“…1 Craniomaxillofacial (CMF) fractures represent a significant component of overall trauma in low‐ and middle‐income countries (LMICs). 2 Open reduction internal fixation (ORIF) is the gold standard for CMF fractures, but patients in LMICs must purchase their own plating supplies. As a result, less than 20% of these patients undergo ORIF for CMF fractures.…”
mentioning
confidence: 99%